A Spatial Analysis of Inward FDI and Rural-Urban Wage Inequality: Evidence from China - Hao Wang; Jan Fidrmuc; Qi Luo (Center for Economic Studies and ifo Institute (CESifo), 2020)
When investigating the relationship between inward FDI and rural-urban inequality, previous studies overlook the inter-regional interactions. Building on the literature that highlights the significant role of rural-urban migration in inequality, this article investigates spatial spillover effect of inward FDI on the rural-urban wage inequality by utilizing the Spatial Durbin Model (SDM) both in the short run and long run. In particular, we carefully consider the heterogeneity of inward FDI and categorize it with respect to entry modes and sectoral distribution. On the basis of a panel dataset covering 30 provinces in China from 2000 to 2016, our results show that overall the inward FDI should not be blamed for the exacerbation of rural-urban wage inequality. We do not find significant relationship between inward FDI in secondary and tertiary sector while the FDI in primary sector has a slight negative effect. When we separate the FDI according to entry modes, we find that WFE is shown to have a negative effect on the rural-urban wage inequality and this effect is more pronounced in the long run when we conduct a period average estimation. This change also similarly applies to the equity joint ventures.
Keywords: C21; F21; O19; 330; spatial spillovers; foreign direct investment; rural-urban wage inequality; SDM